2017
DOI: 10.1590/1980-4415v31n59a08
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogia Intuitiva da Escola Elementar de Pestalozzi: como se ensinava Aritmética?

Abstract: ResumoEste artigo tem por objetivo compreender o arranjo metodológico no ensino da Aritmética na escola elementar de Pestalozzi. Interessa saber como se ensinava Aritmética na escola elementar pestalozziana? Ao transformar alguns textos de Pestalozzi em documentos, notei que o educador suíço sistematizou uma teoria pedagógica que mudou o estatuto da tríade: aluno-saber-professor. Trata-se de uma pedagogia assentada na atividade do espírito humano manifestada pela intuição. Denominei-a de pedagogia intuitiva. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In other contexts, the IM, for its objective and active characteristic, have shown to be effective for teaching different subjects, especially for children, such as geography 13 and math. 14,15 However, there are no studies in the scientific literature that apply the IM in the teaching of FNE or that study its performance in interventions with different durations.…”
Section: Introductionmentioning
confidence: 99%
“…In other contexts, the IM, for its objective and active characteristic, have shown to be effective for teaching different subjects, especially for children, such as geography 13 and math. 14,15 However, there are no studies in the scientific literature that apply the IM in the teaching of FNE or that study its performance in interventions with different durations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Oliveira (2017), we found that the child, when already familiarized with the exercises proposed in table 1, advanced to the parts of the units, that is, studied the fractions. Pestalozzi (2009, p. 46) tells us that "The straight line is still the simplest and the easiest way here, the one that lends itself best to observation and execution", as, according to Oliveira (2017Oliveira ( , p. 1027, it can be seen in the figure that "Dividing a straight line into equal measures is to make the child observe the parts or fractions of a unit". Soon the fractions also had a table, just like in the study of numbers.…”
Section: Costa Emphasized Thatmentioning
confidence: 86%
“…The use of this board admitted that the child exercised the ability to see the line as a unit and to establish the relationships between these units. Oliveira (2017) tells us that, to reach the first objective, it was necessary to ask the child to reproduce four lines on the blackboard and write the number 4; five lines and write the number 5, and so on, because "reproducing lines was also the time to write numbers" (OLIVEIRA, 2017(OLIVEIRA, , p. 1026. Besides, observing this table, the teacher could ask questions involving operations of addition, subtraction, multiplication and division, mentally, without the need to register the signs (+, -, ×, ÷).…”
Section: A Look At Teaching and Mathematics In Pestalozzimentioning
confidence: 99%
See 2 more Smart Citations